Satisfacción del paciente postoperado con la atención de enfermería en el servicio de cirugía del Hospital II-2 Minsa Tarapoto. Junio-agosto 2012 - Pezo Arteaga, Dolibeth (2012)
The present thesis Satisfaction of the Postoperado patient with the nursing care in the service of surgery the Hospital II-2 Minsa Tarapoto. June-August 2012, It is a simple descriptive study, prospective, transversal whose aim is determine the level of satisfaction of the postoperative patient with nursing care in service of surgery at the Hospital II - 2 MINSA Tarapoto, the sample consisting of 46postoperados open abdominal surgery patients hospitalized in the surgery service of the Hospital II-2 MINSA expected in the month of July they fulfil the inclusion criteria, being the technique sample non-probability convenience, the data were collected through personal interviews using a questionnaire type Likert scale with 35 items, analyzing according to frequency and Averages. Since conclusions we have, that the postoperados patients in surgery of the Hospital II-2 Minsa Tarapoto feel partially satisfied with nursing care 69.6%(32), According to characteristics Partner demographic were mature adults 56.5(26) % aged between 37-47 years 26.1%(12), primary incomplete 34.8%(16) of rural 28.3%(13), married 34.8%(16), who have 3 days of hospitalization 39.1%(18) and 2 days postoperative 39.1%(18), the level of satisfaction in relation to needs was partially satisfied (2.45), in relation to expectations was partially satisfied (2.71), in relation to perceptions was partially satisfied (2.81), In relation to the dimensions there is major satisfaction in the Perceptions (2.81). There is recommended in the hospitable institution and in the Faculty of Infirmary to give him major emphasis to the dictation of courses or workshops relative to the quality of attention and to the professional humanism to achieve the satisfaction of the user and hereby to overcome the expectations of the postoperated on patient, reaching with it the full satisfaction of the client in mention